DEPRESSION IN ELDERLY PEOPLE WITH CHRONIC WOUNDS TREATED AT THE SKIN COMMISSION - Bandeira Correia, Analine Souza; Arruda de Queiroz Lombardi , Camila; Trindade Pereira, Amanda; Maria Cunha, Nilza; Cordeiro Vasconcelos, Selene (Revista Baiana de Enfermagem‏, 2022)
Objective: Verify the occurrence of depressive symptoms in the elderly with chronic wounds. Methodology: A descriptive, cross-sectional, quantitative study conducted with 40 elderly people at a University Hospital, using the Geriatric Depression Scale and a structured questionnaire with sociodemographic, clinical variables, lesion characteristics and a brief history of mental health. Results: There was a predominance of females (72.5%), brown (50.0%), Catholic (65.0%), married (50.0%), with incomplete primary education (55.0%), retired (92.5%), income between 1 and 2 minimum wages (62.5%), metabolic diseases (55.0%) and cardiac diseases (25.0%). The wounds were 55.0% venous ulcers, of which 85.0% are in the lower limb. Regarding the Scala scores, 40.0% presented symptoms suggestive of Depression. The elderly with venous wounds and located in the lower limb presented higher score of the depression median. Conclusion: Venous ulcers of the leg was a risk factor for the occurrence of Depression, which occurred in half of the elderly surveyed. Descriptors: Depression. Wounds. Aged. Health of the Elderly. Mental Health.